Dental Pathologies that Cause Partial Tooth Loss - Burlyk В. (Actual Dentistry, 2025)
Partial tooth loss is one of the most pressing problems in modern dentistry, as it significantly impacts the quality of life for patients and the functionality of the dentofacial system. The need for a profound analysis of dental pathologies that lead to tooth loss determines the relevance of the study. Purpose: to determine the leading dental causes of partial tooth loss. Material and methods. The study employed methods of modern scientific literature analysis, clinical generalization, and systematization of pathological factors. Results. The most common causes of partial tooth loss were analyzed, specifically complications of caries, such as pulpitis and periodontitis, which lead to tooth destruction and its subsequent removal. The influence of periodontal diseases—gingivitis, periodontitis, and periodontitis—on bone tissue resorption and loss of tooth fixation is described. It is noted that traumatic injuries due to accidents and physical exertion can be the direct cause of the loss of one or more teeth. Genetic diseases (amelogenesis, dentinogenesis imperfecta) that cause increased tooth fragility are considered. It is also described how systemic diseases, particularly osteoporosis and diabetes mellitus, negatively impact the state of bone tissue. Particular attention is paid to oncological processes in the oral cavity that destroy both hard and soft tissues. Conclusion. The practical value of the study lies in the formation of a comprehensive approach to the prevention and treatment of partial tooth loss, which will contribute to the improvement of dental care for patients.